Neustonic zooplankton communities across distinct summer water masses in the northern East China Sea - Choi, Jang Han; Kim, Geon; Kang, Yoonja; Kang, Chang-Keun; Kim, Taejin; Soh, Ho Young (Marine environmental research, 2025)
Marine neustonic zooplankton are subject to extreme fluctuations in environmental conditions, including water temperature, salinity, and ocean currents. This study examined the community structure of neustonic zooplankton, focusing on copepods, across distinct continental shelf water masses in the northern East China Sea, where coastal and oceanic waters converge. Neustonic zooplankton samples were collected using a neuston net from three regions surrounding Jeju Island, Korea, during June, August, and September 2021. Environmental parameters, such as water temperature, salinity, size-fractioned chlorophyll a concentrations, and suspended particulate matter, were measured. The neustonic copepod community in each region was categorized into two groups based on water masses: Yangtze River Diluted Water (YRDW) versus the remaining shelf water in June; YRDW versus Tsushima Warm Current (TWC) in August; and mixed waters (South Korean Coastal Water, SKCW) versus TWC in September. The spatial distribution of neustonic zooplankton was primarily influenced by distinct water masses. Coastal indicator species (Paracalanus parvus sensu lato (s. l.), Labidocera rotunda, and Ditrichocorycaeus affinis) were significantly correlated with chlorophyll a concentrations in YRDW and SKCW, conversely, water temperature and salinity were closely associated with the abundance of high-salinity indicator species (Canthocalanus pauper, Temora discaudata, Centropages furcatus, and Undinula vulgaris) in the TWC. Additionally, oceanic indicator species correlated with multiple environmental factors across all water masses. These findings suggest that, during summer, the inflow of YRDW influences the spatial conditions in the study area. Moreover, indicator species can serve as valuable markers of water mass fluctuations. •Community structure of neustonic zooplankton, in northern East China Sea was studied.•Their diversity and dominance vary with spatial distribution of water masses.•Water temperature, salinity, and Chl a are major environmental factors affecting them.